RELEVANSI KONSELING PASTORAL BAGI REMAJA TERHADAP PERUBAHAN FUNGSI KELUARGA KRISTEN - Imanuel Catur Oktanto Suryoadi (IAKN Ambon, 2021)
Life experience is the result of a learning process that a person has gone through and through life experience teaches a person to be more careful in dealing with the realities of life that will occur later. The embodiment resulting from the pastoral counseling process is the adjustment of adolescents who experience changes in their functions in Christian families. And the results of good changes based on God's Word become the main goal for teenagers who are experiencing problems in their families and also become a blessing for people who believe in the Lord Jesus Christ in solving their problems. A teenager who experiences changes in himself and his family, of course, this problem causes quite complicated problems where the teenager must experience changes, both changes in himself and also must accept the reality of changes that must be experienced by his family. Adolescents are individuals who are very vulnerable to all influences, both good and bad, if they do not get good and correct guidance as soon as possible, the impact of changes that occur in adolescents will continue to carry over later in their lives.